Micromagnetic modeling of nanostructures subject to heterogeneous strain fields - Challab, N; Aboumassound, A D; Zighem, F; Faurie, D; Haboussi, M (Journal of physics. D, Applied physics, 2019)
We addressed micromagnetic simulations of strained systems constituted of magnetic nanostructures adherent to compliant substrates. To this end, the Landau-Lifshitz-Gilbert equation is implemented within COMSOL Multiphysics® software in a coupled manner with solid mechanics equations. The resulting code is progressively validated with the help of different well chosen examples. These examples are related to Larmor precession, dipolar interaction for circular and spherical media, magnetization reversal in non-strained nanostructure and the effect of homogeneous strain on magnetization distribution. In particular, a comparison with Nmag micromagnetic code is carried out for a magnetization reversal study. Afterward, the developed code is used to simulate the magnetomechanical behavior of magnetic nanostructures deposited on stretchable substrate. As for the homogeneous-strain case, it is shown that the magnetic reversal phenomenon results from a competition between the shape anisotropy and the magnetoelastic one. Moreover, it emerges that the nanostructure thickness plays an important role in the strain transmission from the compliant substrate to the nanostructure and has an impact on the whole magnetomechanical behavior of such systems.